Urinary Tract Infection Among Children's Under (12) Years Old In Tikrit City - Hussein S. Aswed AL-Qaidi; Thamer M. Jasim; Ibrahim A.Hussein AL_Mazruai (College of Pharmacy / Mustansiriyah University, 2012)
A total of 160 urine samples from patient attendants to Tikrit Teaching Hospital in Tikrit during the priod from 1st June to 30 September 2001 with signs and symptoms suggestive of urinary tract infection .Only 51 urine sample (32%) were positive yielded significant Bacteruria. The result indicated that E.coli was the most frequent organism (41%) and consequently followed by Klebseilla spp., Enterobacter spp. (15.5%) and proteus mirabilus, pseudomonas aeruginosa (10%). Urinary Tract Infections are less common in male than female 19 (12%) and 32 (20%) respectively. Cell was found with bicteria in all the positive cases (the 51 urine sample). Regarding to relation of U.T.I. with age, the result showed that the most frequent infected patient was in age group of (6-8) years in both females and male 9(5.6%) and 5 (3%) respectively .The samples were examined within 30 min, specimens were cultured on blood agar, MacConky agar .and nutrient agar, incubated aerobically at 37oCfor 18-24 hrs. This is a cross section study indicated the Ratio of Urinary tract infections in girls more than boys a ratio of 1:0.6 Culture and sensitivity test of antibiotics were done to recognize the etiological agent and select the suitable antibiotics.